Congenital occipitoatlantoaxial malformation in a Brazilian sport horse foal - Silva, Isabella Eduardo da; Nascimento, Acácia Eduarda de Jesus; Rabelo, Andreza Alvarenga; Torres, Luis Ernesto; Fantini, Priscila; Miranda, Ana Luisa Soares de; Maranhão, Renata de Pino Albuquerque; Ocarino, Natália de Melo; Serakides, Rogéria; Carretta Junior, Moacir; Oliveira, Ayisa Rodrigues (Brazilian Journal of Veterinary Pathology, 2024)
A 12-hour-old Brazilian Sport Horse foal, presenting signs of dysmaturity, was referred to the Veterinary Teaching Hospital from the Universidade Federal de Minas Gerais, Belo Horizonte, Brazil, being hospitalized for nine days before euthanasia. Clinically, neurological signs such as difficulty in maintaining head posture, tetraparesis, and asymmetric ataxia were observed, raising suspicion of cervical vertebrae abnormalities. Radiographic analysis revealed occipitalization of the atlas with asymmetric fusion of the atlas to the occipital bone and dorsal luxation of the axis; all these findings were confirmed at necropsy. Additionally, histopathology revealed axonal degeneration at spinal cord and pons as a result of nervous tissue compression at the atlantooccipital fusion area. Congenital occipitoatlantoaxial malformation (OAAM) was the definitive diagnosis in this case, and, to the best of our knowledge, it is described for the first time on a Brazilian Sport Horse.